Acculturative stress, social support and oral health related quality of life among international graduate students in Malaysian public universities / Hala Fathalla Ben Ghasheer - Hala Fathalla, Ben Ghasheer (2020)
Background: Oral health related quality of life (OHRQoL) reflects the impact of the oral condition on physical, social, and psychological functioning and well-being from an individual’s perspective. It is an important health outcome that is influenced by several factors which together are known as the determinants of health. Psychosocial factors are among many other factors that have a crucial role in shaping oral health. Understanding their role in relation to diminished oral health has gained more interest in recent years since such factors could serve as points of intervention for new oral health promotion strategies. Aim: This study aimed to investigate the relationship of acculturative stress and social support with the OHRQoL among international graduate students in Malaysian public universities. Methods: A total of 312 international graduate students completed a web-based questionnaire, including measures of acculturative stress (ASSIS-36), perceived stress (PSS-4), social support (MSPSS-12), oral health perceptions (global rating item), and oral health-related quality of life (OHRQoL, OIDP-8). The hypotheses of the conceptual model were tested employing structural equation modelling using partial least squares (SEM-PLS) with the support of SmartPLS. Results: Twenty-seven percent (27.1 %) of the variance in OHRQoL was explained by acculturative stress, perceived stress, social support, and oral health perceptions. The path coefficients between oral health perception and OHRQoL was the strongest (β = - 0.385, P < 0.001). Acculturative stress directly influenced OHRQoL (β=0.20, P=0.009), and indirectly through perceived stress (β=0.05, P=0.019). Social support had a moderating effect (t=1.98) on the psychosocial domain of OHRQoL and mediated the relationship between perceived stress and OHRQoL (β=0.046, P= 0.02). The overall predictive power of the model was 23 %. Conclusion: Results indicated that acculturative stress, perceived stress, and social support are among the predictors of OHRQoL. Oral health perceptions and iv acculturative stress were the most significant predictors that contributed the largest amount to the model. The findings emphasize the potential role of psychosocial factors in relation to oral health. The empirical evidence of this study could facilitate the planning of targeted strategies by incorporating stress reduction and social support enhancement. Such strategies might be a new promising way to enhance OHRQoL since these elements can be modified and response to interventions. Keywords: OHRQoL - Acculturative stress – Perceived stress- Social supportInternational students - Malaysia - Structural Equation Modelling